2020
DOI: 10.1021/acs.organomet.0c00564
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the Structural and Electronic Properties of NHCs with Bicyclic Architectures

Abstract: Quantification of the steric and electronic properties of ligands is an important task for the development of highly effective chemical transformations when using a metal complex as a catalyst. In this study, we used silver and iridium complexes to perform systematic analyses to quantify the steric and electronic properties of original NHCs, which we refer to as DHASI and BCPSI. In addition to two silver chloride complexes that we previously reported, two novel BCPSIiPrAgCl and BCPSICyAgCl complexes were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…For comparison with the previous reports, the results from the measurements using nujol were referenced. Calculations showed that the electron-donating ability of the saturated NHO 3 was lower than those of the known unsaturated NHOs (Figure S13) but higher than the corresponding NHC ligand (the TEP value of DHASI i Pr using the Ir scale in CH 2 Cl 2 was 2053). The cationic charge of the ylide is stabilized via delocalization through a 6π aromatic system in the case of unsaturated NHOs, which is not the case for saturated NHO ligands (Figure a); therefore, compared with their saturated counterparts, the unsaturated NHO ligands obviously donate more electrons to the bound rhodium.…”
Section: Resultssupporting
confidence: 85%
“…For comparison with the previous reports, the results from the measurements using nujol were referenced. Calculations showed that the electron-donating ability of the saturated NHO 3 was lower than those of the known unsaturated NHOs (Figure S13) but higher than the corresponding NHC ligand (the TEP value of DHASI i Pr using the Ir scale in CH 2 Cl 2 was 2053). The cationic charge of the ylide is stabilized via delocalization through a 6π aromatic system in the case of unsaturated NHOs, which is not the case for saturated NHO ligands (Figure a); therefore, compared with their saturated counterparts, the unsaturated NHO ligands obviously donate more electrons to the bound rhodium.…”
Section: Resultssupporting
confidence: 85%
“…The bonds lengths in the coordination sphere of the two distinct iridium atoms are similar to those observed in related complexes. [52][53][54][55] Typically, the Ir-C(cod) bond lengths of a trans-olefin is 10 pm longer than for the respective cis-olefin due to the trans-effect of the NHC ligand, which is also observed for [(IrCl(cod)) 2 (9)].…”
Section: Dalton Transactions Papermentioning
confidence: 78%
“…To estimate the steric demands of new ligands, we calculated their Tolman cone angles θ as a widely accepted steric descriptor by the reported method, using semiempirical quantum mechanical AM1 techniques with full optimization of geometrical parameters . The obtained data (Table S1) show that their steric demands vary over a rather wide range between 128 and 193°, peaking in each of the three ligand groups at compounds L1c , L2c , and L3b , respectively.…”
Section: Resultsmentioning
confidence: 99%